2020
DOI: 10.3390/molecules25246001
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interaction Disruptors of the YAP/TAZ-TEAD Transcriptional Complex

Abstract: The identification of protein-protein interaction disruptors (PPIDs) that disrupt the YAP/TAZ-TEAD interaction has gained considerable momentum. Several studies have shown that YAP/TAZ are no longer oncogenic when their interaction with the TEAD family of transcription factors is disrupted. The transcriptional co-regulator YAP (its homolog TAZ) interact with the surface pockets of TEADs. Peptidomimetic modalities like cystine-dense peptides and YAP cyclic and linear peptides exploit surface pockets (interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…It retained hydrophobicity-driven interactions with Lys274 for TEAD1 with electrostatic forces of −7.356 kcal/mol. Moreover, as described above, YAP Ser94, Phe96, Arg89, and Phe95 have been revealed as critical binding residues in YAP-TEAD1 PPIs by previous mutagenesis studies [26,29,30,59,63,64]. Phe96 interacts with Lys274 via electrostatic interactions.…”
Section: Analysis Of the Yap-tead1 Interaction At Interface 3 With Fmo Calculationmentioning
confidence: 75%
“…It retained hydrophobicity-driven interactions with Lys274 for TEAD1 with electrostatic forces of −7.356 kcal/mol. Moreover, as described above, YAP Ser94, Phe96, Arg89, and Phe95 have been revealed as critical binding residues in YAP-TEAD1 PPIs by previous mutagenesis studies [26,29,30,59,63,64]. Phe96 interacts with Lys274 via electrostatic interactions.…”
Section: Analysis Of the Yap-tead1 Interaction At Interface 3 With Fmo Calculationmentioning
confidence: 75%
“…Therefore, pharmacological development of TAZ inhibitors for cancer treatment deserves a great deal of attention with respect to prediction of toxicity and side effects on tissue homeostasis. It is indispensable to develop selective inhibitors or activators that target specific binding sites between TAZ and its interacting partner, which may not interfere with normal tissue homeostasis and may contribute to desirable therapeutic effects (Pobbati and Rubin 2020). Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The third interface assumes importance because it determines the affinity of binding between molecular partners, while the second interface is home of peptides and small molecules bindings that may act as disruptor of YAP/TEAD interaction. These works are carried out by Hong et al and Pobbati et al groups who recently identified another pocket, showed as target for drugs with great potential in the impairment of YAP/TEAD complex formation [ 30 , 31 ].…”
Section: The Hippo Pathway Corementioning
confidence: 99%